Optimal damper placement in hybrid control system of multiple isolation and building connection. (2017) - Tamura, Goki; Taniguchi, Masaki; Fujita, Kohei; Tsuji, Masaaki; Takewaki, Izuru
An algorithm for optimal damper placement is proposed in a hybrid control system of multiple isolation and building connection. Such innovative hybrid control building system has been proposed recently. It is a great concern whether the seismic displacement response at the base-isolation layer of the existing base-isolated buildings may be amplified under long-period and long-duration ground motions. In order to enhance the robustness on the seismic performance of those base-isolated buildings, a novel hybrid system of multiple isolation and building-connection has been proposed and compared with other structural systems such as an independent multiple isolation system, a hybrid system of base-isolation and building-connection in the previous paper. It has been made clear that such hybrid control system possesses a remarkable performance for various types of earthquake ground motions. After the investigation of the effective location of the middle isolation story, a sensitivity-based optimisation algorithm is proposed for optimal connection damper placement in such hybrid control system.